Heavy Metal Resistance in Salmonella Typhimurium and Its Association With Disinfectant and Antibiotic Resistance - Mustafa, Ghulam Raza; Zhao, Ke; He, Xueping; Chen, Shujuan; Liu, Shuliang; Mustafa, Ahsan; He, Li; Yang, Yong; Yu, Xiumei; Penttinen, Petri; Ao, Xiaolin; Liu, Aiping; et al. (Frontiers in Microbiology, 2021)
Abstract Metals are widely used in animal feed for their growth-stimulating and antimicrobial effects, yet their use may potentially promote the proliferation of antibiotic resistance through co-selection. We studied the prevalence and associations of metal, antibiotic and disinfectant resistances of 300 Salmonella Typhimurium isolates from pig meat, pig manure, chicken meat, poultry manure and human stool from Sichuan, China. 74% of the 300 Salmonella Typhimurium isolates were considered resistant to Cu, almost 50% to Zn and Cr, over 25% to Mn and Cd, and almost 10% to Co. Most of the isolates carried at least one heavy metal resistance gene (HMRG). The Cr-Zn-Cd-resistance gene czcD was carried by 254 isolates and the Cu-resistance genes pcoR and pcoC by 196 and 179 isolates, respectively. Most of the isolates were resistant to at least one antibiotic and almost 80% were multidrug-resistant. The prevalence of resistance to six antibiotics was higher among the pig meat and manure isolates than among other isolates, and that of streptomycin and ampicillin were highest among the pig meat isolates and that of ciprofloxacin and ofloxacin among the pig manure isolates. From 55% to 79% of the isolates were considered resistant to disinfectants triclosan, trichloroisocyanuric acid or benzalkonium chloride. The metal resistances and HMRGs were associated with resistance to antibiotics and disinfectants. Especially, Cu-resistance genes were associated with resistance to several antibiotics and disinfectants. The transfer of the Cr-Zn-Cd-resistance gene czcD, Cu-resistance gene pcoC and Co-Ni-resistance gene cnrA into Escherichia coli and the increased Cu-resistance of the transconjugants implied that the resistance genes were located on conjugative plasmids. Thus, the excessive use of metals and disinfectants as feed additives and in animal care may have the potential to promote antibiotic resistance through co-selection and maintain and promote antibiotic resistance even in the absence of antibiotics.